Evasão no curso de licenciatura em matemática da Universidade Tecnológica Federal do Paraná - câmpus Curitiba - Ramos, Bianca (2017)
This work intends to identify the causes for dropouts in the Undergraduate Degree in Mathematics at the Federal University of Technology - Paraná, on the Curitiba Campus. We employed a qualitative research in a descriptive approach, utilizing the data collected from the University's Academic System and a questionnaire applied to the dropout students, in order to identify the personal, internal, and external causes related to this phenomenon (BRASIL, 1996). The analysis of the data collected was based on authors such as Adachi (2009), Biazus (2004), Castro (2013), Santos (2012), and Silva (2009). After analyzing the results obtained, we highlight a few of the causes that most afflict the undergraduate students of Mathematics at UTFPR, such as interest in another undergraduate degree; discouraging perspectives regarding the future occupation; the decline of teaching jobs; the morning schedule of the classes; professors who do not meet expectations. However, we also present a few actions aiming to minimize the dropout rate in our course, which is at 96.9%.